Cost optimization for flexible pavement on fine sand improved using palm fibers - Ahmed H. Elbosraty; M. Bahr; Ahmed M. Ebid (Scientific Reports)
Abstract Improving the CBR value of the fine sand sub-soil layer is critical for enhancing flexible pavement roads’ stability and cost efficiency. This study investigates the impact of mixing fine sand with palm fibers on its CBR value in order to minimize the total cost. Experimental tests were conducted considering different palm fiber contents (0.5%, 1.0%, and 1.5% by weight), and the results indicate that the maximum CBR value of 25% was archived using palm fiber content of 1.0%. Beyond this content, a decline in CBR was noted due to fiber clustering. The AASHTO Pavement Design Guide was used to investigate the impact of enhancing the sub-soil CBR value on the thickness and the cost of the base and sub-base layers for both urban and rural roads. The results showed that increasing the CBR value reduces both the thickness and the costs of these layers. In addition, the option of using a sub-base layer is more cost effective for rural roads on weak soil (CBR < 20%) and for high-traffic urban roads. Finally, a cost analysis study was conducted to optimize the total cost of soil improvement and (base & sub-base) layers. The outcomes indicated that the cost-effective CBR values are ranged between (13% & 17%) for rural roads and (17% and 19%) for urban roads. These values are equivalent to palm fiber content of (0.17% & 0.33%) for rural roads and (0.33% & 0.43%) for urban roads. Although this study showed that using organic reinforcement like palm fibers is a sustainable, economical, and eco-friendly solution, its durability and environmental degradation should be investigated.